Kosmologi dalam Tafsir Al-Ibriz Karya Bisri Mustafa: Relasi Tuhan, Alam dan Manusia - Muhammad Roziqin Yusuf; Mukh Nursikin (Journal on Education, 2023)
From a Javanese perspective, cosmology is very important for mastering all functional concepts of the world. This concept enlivens every perception and every action in the Javanese worldview, even in the field of Qur'an interpretation. Bisri Mustafa's Al Ibriz is one of his interpretations that consistently reveals his identity as a Javanese interpretation. Based on this, the aim of this study is to find a cosmological understanding of Al-Ibriz's interpretation. To achieve this goal, this study uses a kind of descriptive analysis technique for literature review. The study also uses data analysis techniques using the Hans-Gerk-Gadamer interpretation method. As a result of the discussion, it was found that in Al-Iblitz's interpretation, the relationship between God, nature and humans is described through human behavior in the real world. As the center of reality, humans have a duty to maintain the world and make the most of it. Therefore, people should always worship God and build relationships with others. This behavior is an attempt to maintain balance and peace in life in the real world, and it also affects the afterlife.